Gender, equality and education from international and comparative perspectives - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (Emerald Group Pub., 2009)
This volume of "International Perspectives on Education and Society" investigates the often controversial relationship between gender, equality and education from international and comparative perspectives. Much has been written recently about the global progress made toward gender parity in enrolment and curriculum in nations around the world. And there is much to tout in these areas. Although gender parity is not yet the global norm, the expectation of gender equality increasingly is. Some have gone so far as to say that the global expansion of modern mass schooling has created a world culture of gender equality in education. Yet, while there have been many positive advances regarding girls' and women's education around the world, there are still significant differences that are institutionalized in the policies and administrative structures of national education systems. For example, some of the strongest evidence of gendered inequality in schooling is the fact that in many developing countries there are large proportions of school-age children who are not in school - many if not most of whom are girls. The question this volume investigates is whether gender equality in education is really being achieved in schools around the world or not.
Keywords: Educational equalization.; Sex discrimination in education.; Comparative education.; Education -- International cooperation.; Education and globalization.; Education.; Social groups.; Education -- General.; elektronické knihy; electronic books